Ionic contrast terahertz near-field imaging of axonal water fluxes - Masson, Jean-Baptiste (National Academy of Sciences, 2006)
We demonstrate the direct and noninvasive imaging of functional neurons by ionic contrast terahertz near-field microscopy. This technique provides quantitative measurements of ionic concentrations in both the intracellular and extracellular compartments and opens the way to direct noninvasive imaging of neurons during electrical, toxin, or thermal stresses. Furthermore, neuronal activity results from both a precise control of transient variations in ionic conductances and a much less studied water exchange between the extracellular matrix and the intraaxonal compartment. The developed ionic contrast terahertz microscopy technique associated with a full three-dimensional simulation of the axon-aperture near-field system allows a precise measurement of the axon geometry and therefore the direct visualization of neuron swelling induced by temperature change or neurotoxin poisoning. Water influx as small as 20 fl per μm of axonal length can be measured. This technique should then provide grounds for the development of advanced functional neuroimaging methods based on diffusion anisotropy of water molecules.